The Role of Member Participation and Governance on Sustainability: Evidence from Cooperatives in South Aceh - Putri, Cut Eka Rosnika; Indriani, Mirna; Indayani, Indayani (Journal of Accounting Research, Organization and Economics, 2022)
Objective The purpose of this study is to find out the determinants of cooperative sustainability in the cooperatives of South Aceh District, Aceh, Indonesia. The dependent variable in this study is cooperative sustainability, while the independent variables include participation of cooperative members and cooperative governance.Design/methodology The population in this study were all cooperative employees in South Aceh Regency. Purposive sampling was used to draw the samples in this study which consist of all registered cooperatives in South Aceh with the criteria of active cooperatives as many as 157 cooperatives. Respondents in this study were chairman and treasurer totaling 314 respondents. Multiple linear regression analysis was used to test the hypotheses.Results The results of this study indicate that the participation of members and the government simultaneously affect the sustainability of cooperatives in South Aceh. Furthermore, partially the participation variables of cooperative members and governance variables affect the sustainability of cooperatives in South Aceh.